The Eye of Surveillance - N. Price (Law Text Culture, 2008)
Within the theme of tactics against fear I am interested in the paranoia that fear tends to generate for the ordinary person as well as for all-powerful institutions. I took the computer and explored it in relation to surveillance and paranoia, or rather explored the question ‘Is computerised surveillance for my protection?’